School Libraries in the Digital Age: Digitization Against Library Anxiety - Arany-Nagy, Zsuzsanna (Bobcatsss, 2023)
The society of the 21st century is a witness of digital transition in our history. The information is available for anyone online and offline too, because of the results of these changes. Nowadays the environment which provides access to information is more complex like the methods used in the past. The types of the information carriers are changed, and so are the channels of communication. The exclusivity of printed sources is ceased because of the internet, which is the beginning of the homogenized information. In the digital world the amount of available information grew which is the result of easier, faster publication and the blurring of the role of authors and consumers. Because of these, the appearance of diseases caused by too much available information is nowadays more frequent. The 21st century’s information diseases – like library anxiety, information anxiety or information overload – are indicators of one species of fear and anxiety. These diseases are primarily detectable in university students. The fear of using a library, or information anxiety could have strong influence on students’ learning performance (Mellon, 1986). Information overload, the feeling of anxiety caused by too much available information are not new, nor eternal things. We can talk about it since Gutenberg, and the spread of printed books; namely that was the first time when people thoughtt about information like there is too much of it and an average person cannot read and learn all of it in his or her lifetime. In my research I deal with library anxiety detailed, especially school libraries. The inspiration came from my workplace which is a school library in an elementary- and high school. In my experience the 11-17 years old children it is hard to make them a library user. This experience confirmed by the statistics of Hungarian Library Institute. In my research I look for the answer why do not use the school library the 11-17 years old people. Though library anxiety proved by research, but mostly at senior or graduate students. At public education there is no research about it yet. The theme is not a new thing, which is proved, since the 1980s there are new pieces of literature. I search for the answer, how digitization can help reduce library anxiety.